The assessment of present, past and future climatic variability in the americas from tree-line environments - Luckman, Brian H. (2001)
In this note we introduce one of 14 Collaborative Research Networks (CRN) funded by the Inter-American Institute for Global Change Research. It was established in 1999 and involves 15 principal investigators from 13 institutions in Canada, USA, Mexico, Bolivia, Chile and Argentina. The primary goals of the project are (i) to develop a network of tree-ring chronologies from climatically-sensitive treeline sites in the western American Cordillera and (ii) to use these data to reconstruct and compare regional interannual to decadal climate variability along the PEP-1 transect from Alaska to Tierra del Fuego. The project also seeks to enhance the development and utilization of dendrochronology for tropical mountain tree species and expand collaboration, training and the application of paleoenvironmental science within Latin America to address the issues of climate variability and change.